2008
DOI: 10.1097/tp.0b013e31817c6447
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of BK Virus in Renal Allograft Recipients: Independent Risk Factors for BK Virus Replication

Abstract: BACKGROUND Identification of risk factors for BKV replication may improve transplant outcome. We investigated the impact of immunosuppressive drugs on the prevalence of BKV replication in recipients of human renal allografts. METHODS One hundred twenty renal allograft recipients were studied prospectively at one, three, and six months post-transplantation to identify risk factors for BKV replication. BKV replication was quantified by measurement of urinary cell BKV VP1 mRNA levels using BKV specific primers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 29 publications
8
92
2
Order By: Relevance
“…PyVAN affects up to 10% of kidney transplant recipients, and the rate of renal allograft loss varies from 10% to 80% (41,42). About 30%-50% of kidney transplant recipients with high-level viruria progress to BKV viremia and PyVAN (40).…”
Section: Bk Polyoma Virus Infectionmentioning
confidence: 99%
“…PyVAN affects up to 10% of kidney transplant recipients, and the rate of renal allograft loss varies from 10% to 80% (41,42). About 30%-50% of kidney transplant recipients with high-level viruria progress to BKV viremia and PyVAN (40).…”
Section: Bk Polyoma Virus Infectionmentioning
confidence: 99%
“…Studies report various agents such as antirejection treatment regimens with pulse steroid, 11 steroid use and antithymocyte globulin induction therapy, 12 high level of tacrolimus, 13,14 and mycophenolate mofetil, 14,15, as being responsible for the emergence of BK viremia and viruria. In our study, no statistically significant association was found between the type of immunosuppressant and BK virus positivity.…”
Section: Discussionmentioning
confidence: 99%
“…BKV associated nephropathy affects 1-10% of renal transplant recipients and linked to the strength of the immunosuppression. Higher incidence of BK viremia is related to a higher dose of rabbit ATG [72][73][74][75].…”
Section: Bk Virus (Bkv)mentioning
confidence: 99%